Collaborative Govenance in Preserving the Malay Culture of Riau - Afandi, Syed Agung; Lestari, Reski; Afandi, Muslim (SCAD Independent, 2021)
The Riau Government is committed to preserving the Riau Malay Culture as stated in the Riau Vision 2025. The current facts show that there is a severe weakening of the Malay Culture in Riau Province. This can be seen from the ethics, grammar, fashion, culinary, art, and Malay traditions that the Riau Malay community is starting to leave. The purpose of this study was to determine collaborative governance in the effort to preserve the Riau Malay Culture. The research method used is qualitative. The results of this study indicated that the Riau Government is not committed to achieving its vision, which is reflected in government policies. Lack of a roadmap for a cultural vision so that a network structure between stakeholders was not formed, the master plan owned by each stakeholder was not integrated, and was not interdependent, did not have a standard measure that describes procedures and authority in action, there was no function of joint decision-making and sharing of responsibilities, and there was no communication and flow of information between stakeholders so that collaborative governance in the preservation of Riau Malay culture was not carried out.